In vitro evaluation of anti-angiogenesis property of anti-VEGFR2 nanobody-conjugated H40-PEG carrier loaded with methotrexate - Seyed Masih Adyani; Hamid Rashidzadeh; Mahdi Behdani; Seyed Jamal Tabatabaei Rezaei; Ali Ramazani (Iranian Journal of Basic Medical Sciences, 2022)
Objective(s): In this study, Boltorn® H40-PEG-MTX-anti-VEGFR2 nanobody was fabricated in which nanobody was selected for blocking the receptor, H40 as a nanocarrier for delivery of methotrexate (MTX) to the tumor cells, and polyethylene glycol (PEG) moieties for improving the blood circulation time and safety. Materials and Methods: The synthesis process of the nanosystem has been characterized by different analytical methods. Results: The prepared nanoplatform exhibited high drug loading capacity, excellent colloidal stability, and an average particle size of around 105 nm. MTX was successfully conjugated through ester bonds and its release profile clearly showed that the ester bond is in favor of releasing the drug in acidic pH (5.5). The cytotoxicity of the developed nanoplatform exhibited great anti-cancer activity against MCF7 and KDR293 (cells with overexpressed anti-VEGFR2 NB receptors) cell lines while no deleterious toxicity was observed for nanocarrier against HEK293 normal cells.  Furthermore, both hemolysis and LD50 assay results confirmed the hemocompatibility and biocompatibility of the developed nanoplatform. Conclusion: The most striking result to derive from the data is that the designed nanoplatform could potentially inhibit cell migration and invasion and the anti-angiogenesis properties of the developed nanoplatform may serve as a promising nanosystem to suppress the formation of blood vessels around tumor cells and consequently inhibit tumor progression.